Difluorocarbene enables to access 2-fluoroindoles from ortho-vinylanilines - Jianke Su (Nature Portfolio, 2021)
2-Fluoroindoles are an important structural scaffold in many bioactive or therapeutic agents, but efficient constructions of 2-fluoroindole derivatives are very sparce. Here the authors report an efficient and general strategy for the construction of 2-fluoroindoles in which a wide variety of 2-fluoroindoles were accessed with high efficiency and chemoselectivity.